Risk Factor Analysis of Drug-Resistant Tuberculosis in Tuberculosis Patients at Level II Health Facilities in Depok City - Anisa Rachmita Arianti; Syamsudin Syamsudin; Ros Sumarny; Lusi Nursilawati Syamsi (PT Mattawang Mediatama Solution, 2024)
Based on Global Tuberculosis Report In 2022, Indonesia will be among the 10 countries contributing to the highest incidence of drug-resistant tuberculosis each year. There are 12,794 cases of drug-resistant tuberculosis in Indonesia with 7,884 cases starting treatment. The number of drug-resistant tuberculosis cases involves a variety of risk factors. This study aims to analyze the risk factors associated with drug-resistant tuberculosis. The research method is observational analytic design case control study. The research samples were patients with drug-resistant tuberculosis and drug-sensitive tuberculosis in Depok City Health Facilities for the period March 2022–May 2023. Data were collected using questionnaires and SITB (Tuberculosis Information System). Bivariate analysis using Chi Square, while multiple logistic regression multivariate analysis. The results of the study of 73 cases and 73 controls showed that the majority were aged 18 - 65 years, 89% of cases and 62% of controls, male gender was the most dominant, 64.4% of cases and 52% of controls, most of the respondents did not work 68.5 % of cases and 53.4% ​​of controls, most of them had low income, 82.8% of cases and 62% of controls. Most of the case group had a high level of education, namely 58.5%. Meanwhile, most of the control group had low education, 50.7%. Bivariately, risk factors associated with drug-resistant tuberculosis are HIV, history of previous treatment, adherence to taking medication and the role of drug swallowing supervisor (PMO). Based on multivariate analysis, the dominant variable associated with the incidence of drug-resistant tuberculosis is history of previous treatment (OR6.021 with CI 2.055-18.721) meaning that patients with a history of previous treatment have a 6 times risk of developing drug-resistant tuberculosis compared to patients without a history of previous treatment.